2020
DOI: 10.1021/acs.chemmater.0c01735
|View full text |Cite
|
Sign up to set email alerts
|

A “Tips and Tricks” Practical Guide to the Synthesis of Metal Halide Perovskite Nanocrystals

Abstract: Metal halide perovskite nanocrystals offer a range of interesting properties and are being studied extensively for applications in solar cells, photodetectors and light-emitting devices. This perspective provides a number of best practices for the synthesis, purification, and characterization of metal halide perovskite nanocrystals, with detailed discussion of CsPbI3, CsPbBr3, CH3NH3PbI3 (MAPI), and Cs2AgBiBr6 as examples. The choice of reactants and ligands for hot-injection reactions are discussed, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
167
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(182 citation statements)
references
References 109 publications
4
167
0
Order By: Relevance
“… 3 , 9 , 10 In these systems, various works have shown that their surface passivation, via a proper choice of surfactants, plays a fundamental role in achieving both colloidally stable and strongly emissive LHP NCs. 9 , 11 Aliphatic amines and carboxylic acids (most often oleylamine and oleic acid) are the standard ligands employed in the synthesis of these NCs, eventually passivating their surface as charged species (as ammonium and carboxylate ions, respectively). Various studies have demonstrated that a simple variation of the local pH, which can cause protonation/deprotonation of carboxylate/oleylammonium ions, or even a dilution of the NC suspension, which decreases the chemical potential of the free ligands with respect to that of bound ones, can lead to ligands detachment, which is deleterious for both colloidal stability and PL.…”
mentioning
confidence: 99%
“… 3 , 9 , 10 In these systems, various works have shown that their surface passivation, via a proper choice of surfactants, plays a fundamental role in achieving both colloidally stable and strongly emissive LHP NCs. 9 , 11 Aliphatic amines and carboxylic acids (most often oleylamine and oleic acid) are the standard ligands employed in the synthesis of these NCs, eventually passivating their surface as charged species (as ammonium and carboxylate ions, respectively). Various studies have demonstrated that a simple variation of the local pH, which can cause protonation/deprotonation of carboxylate/oleylammonium ions, or even a dilution of the NC suspension, which decreases the chemical potential of the free ligands with respect to that of bound ones, can lead to ligands detachment, which is deleterious for both colloidal stability and PL.…”
mentioning
confidence: 99%
“… 33 36 While our knowledge of the surface passivation of Pb-based perovskite NCs is reaching maturity, we know much less on the ligand shell of double perovskite NCs. 14 , 37 41 To date, only the ligand shell of Cs 2 AgBiBr 6 NCs has been examined by Zhang et al, who concluded that the only species passivating the surface are alkylammonium ions. 14 …”
mentioning
confidence: 99%
“…[ 115 ] In addition, the attaining isolation between the nucleation and growth stages endows the synthesized lead‐free HDP nanocrystals with a narrow size distribution. [ 116 ] In 2015, Protesescu and co‐workers first introduced the high temperature hot injection method to successfully synthesize CsPbX 3 perovskite nanocrystals. [ 24 ] This method can also be employed to prepare lead‐free HDP nanocrystals with some modification due to the similar features of the perovskite family.…”
Section: Strategies For Boosting the Efficiency Of Halide Double Peromentioning
confidence: 99%
“…It was noteworthy that the nucleation and growth of nanocrystals by injecting trimethylsilyl bromide(TMSBr) were obviously faster than that of Cs‐oleate injection. [ 116 ] However, the prepared Cs 2 AgBiX 6 (X = Cl, Br) nanocrystals exhibited weak and broad PL emission as well as extremely low PLQY . Subsequently, Lamba et al.…”
Section: Strategies For Boosting the Efficiency Of Halide Double Peromentioning
confidence: 99%